Haploinsufficiency for Steroidogenic Factor 1 Affects Maternal Behavior in Mice - Spanic, Tanja; Grgurevic, Neza; Majdic, Gregor (Frontiers in Behavioral Neuroscience, 2016)
Steroidogenic factor 1 (SF-1), officially designated NR5A1, is essential for gonadal and adrenal development and for the normal structure of the ventromedial hypothalamus, as demonstrated by SF-1 knockout mice (SF-1 KO), but much less is known about the possible effects of haploinsufficiency of the SF-1 gene. In the present study, maternal behavior in SF-1 KO heterozygous mice was evaluated. Behavioral tests revealed that SF-1 KO heterozygous females have impaired maternal behavior. In comparison to WT females, SF-1 KO heterozygous females retrieved significantly fewer pups into their nests, latency to retrieve and crouch over the pups was longer, and their nests were lower quality. As suggested by previous studies full dosage of SF-1 gene is needed for appropriate stress response and expression of BDNF in the brain, and this might present a mechanism through which maternal behavior in SF-1 KO heterozygous females is impaired.